1998
DOI: 10.1109/68.669242
|View full text |Cite
|
Sign up to set email alerts
|

Novel bias control of electroabsorption waveguide modulator

Abstract: Abstract-A novel approach is proposed for controlling the bias of an electroabsorption waveguide modulator for maximum radio-frequency (RF) gain in analog fiber-optic links. It is based upon the correlation between the RF gain and the modulator dc photocurrent. It is found that, under various operating conditions, the modulator bias at which the modulator dc photocurrent experiences the largest change with incremental bias, coincides with the bias for the maximum RF gain. This approach eliminates the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…This is because RF link gain is proportional to the square of the modulator slope efficiency, and modulator photocurrent is a measure of the modulator transmission as long as the modulator is not saturated. Therefore, tracking the dc photo current of the modulator and keeping its bias sensitivity maximum keeps the RF link gain maximum [42]. This was found to be the case for different input polarizations, wavelengths and power levels.…”
Section: A Lumped Ea Modulatorsmentioning
confidence: 88%
See 1 more Smart Citation
“…This is because RF link gain is proportional to the square of the modulator slope efficiency, and modulator photocurrent is a measure of the modulator transmission as long as the modulator is not saturated. Therefore, tracking the dc photo current of the modulator and keeping its bias sensitivity maximum keeps the RF link gain maximum [42]. This was found to be the case for different input polarizations, wavelengths and power levels.…”
Section: A Lumped Ea Modulatorsmentioning
confidence: 88%
“…Recently, it was shown that the bias where the slope of the dc photo current is largest coincides with the bias point that achieves the maximum RF link gain [42]. This is because RF link gain is proportional to the square of the modulator slope efficiency, and modulator photocurrent is a measure of the modulator transmission as long as the modulator is not saturated.…”
Section: A Lumped Ea Modulatorsmentioning
confidence: 98%
“…As shown in Figure 1a, the output intensity of the MZM is distorted by the phase (bias) drift θ dri f t , which is mainly caused by temperature changes and the photorefractive effect [30,50]. This negatively affects the performance of a QKD system that requires precisely defined pulse intensities.…”
Section: Methodsmentioning
confidence: 99%
“…When φ changes the transfer function of the EOM is shifted accordingly, to the right or to the left, during the operating time. The drift of the EOM transfer function can be explained by different effects such as changes of working temperature, optical coupling efficiency and photo refractive effects [5,6,7,8].…”
Section: The Electro-optic Modulatormentioning
confidence: 99%